Diagnóstico e avaliação de acesso a políticas públicas por agricultores familiares em comunidades rurais no município de Paragominas - COLONNELLI, Breno Lima (2020)
Understanding local, cultural, social, economic, political, and environmental factors is important to create public policies that cause a positive impact to farmers in Paragominas. Thus, this work aims to survey the current scenario of Paragominas small scale farmers access to existing public policies, analyzing different dimensions of the diagnosis and correlating them to land, agrarian, social, environmental and economic issues existing in Paragominas rural communities. In addition, we sought to identify how they contribute to local development to propose mechanisms for farmers to access the current public policies. The following procedures were necessary to support the objectives proposed in this research: Bibliographical review of rural diagnosis, public policy and rural and sustainable development data, followed by the application of a survey. Data collection was done by interviewing 309 families distributed in 32 rural locations in Paragominas, where semi-structured questionnaires were applied, seeking to collect information divided into sessions: Personal data, family composition, property data, social organization data, land usage data, environmental data and public policies. The results show that 27% of the interviewed people are over 59 years old and 65% are between thirty and 59 years old. They are mostly from other towns in the State of Para. For 53% of the participants have been over ten years since they arrived where they are. As for the level of education, it follows the national average with a low level of education, however 69% consider access to education to be good or excellent. Health posts are the main resource for treating diseases for 69% of respondents. It is observed that 67% of respondents participate in some social organization, 71% for more than 5 years and in 86% of cases that is beneficial to sell their products. However, only 36% say they have changed the way they produce after joining the association and / or cooperative and 34% of the production is sold by the association. The land and economic situation are still worrying, since 31% declare themselves to be squatters and 61% live with up to one minimum wage. As for access to public production policies, only 31% accessed some type of program, of which 61% is represented by Pronaf A and 94% did not have access to government procurement programs.